Find the fuzzy maximum flow of Imam Kadhimen visitors using fuzzy dynamic programming University of Baghdad - Faculty of Administration and Economics - خلف وقاص سعد; حليم حسين داود (Journal of Economics and Administrative Sciences, 2018)
Baghdad and the other Iraqis provinces have witnessed many of celebrations which have the significant effect on the souls of Arabic and Islamic people in general , and Iraqi people, especially the birthday and death of two al-kadhimen Imams(peace upon them) and others .From here the researcher begin to study the visiting of imam kadhimen (peace upon him) on 25 Rajab the commemoration of his sacrifice, simply because have implications of religious, ideological and cultural sectors which represents in finding the greatest flow of visitors .the problem of research appeared due to the clear difference in number of visitors during one day, beside the significant increase in number of visitors through the period of visiting that reached great number on days (22-23-24 of Rajab month), also the researcher has chosen the sample of research, depending on the number of visitors in Sadir city and their neighborhoods to city of holy kadhimen, in order to identify the Maximum flow of visitors in coordination with concerned sides (Shitte affairs divan /Department of religious ceremonies /board of Al-husyania procession), (the general secretariat of holy shrine of kadhimen), (Council of Baghdad province/ governor of Sadir city 1,2), (councilarity of Baghdad /department of designs /section of geographical information), in addition to many of friends who are living near the place which leads to location of visiting ,beside the number of visitors who they done the ceremony of visiting during its time. The goal of study is to find the greatest flow of visitors with create treatment of fuzzy by using the method of fuzzy dynamic programming style, though it used rank function to solve the fuzzy and Trigonometric functions, in order to know the time of increasing number of visitors .The results which have gotten by research that the Maximum flow of visitors on 24 Rajab are (131196, 94100, 46056), Throw( Morning, afternoon, evening) Where the number (46056) represents the Maximum flow for the morning period and so on the rest of the numbers, By using the grade function of the triangular triangulation function to handle the fog of the three periods of visitors per day (Ie after processing the fog for (22-23-24 of Rajab month) shows that the Maximum flow of the processor is (91391) visitor at day 24), exactly the flow of visitors have increased from or fly intersection to Tarik intersection ,to 55 intersection, to 83 intersection, intersection of complex of teachers ,intersection of oil club, to al– binok, to selekh intersection, to al-nada mosque, to Antar intersection, to intersection of 14 Ramadan bridge, finally passing to kadhimen city .The number of visitors are (131196-51084), and the time of visiting between the noon of 23 of Rajab to night 24 of Rajab As shown in Figure (11).